2008
DOI: 10.1016/j.cell.2008.09.060
|View full text |Cite
|
Sign up to set email alerts
|

Neurofibromin Regulation of ERK Signaling Modulates GABA Release and Learning

Abstract: Summary We uncovered a new role for ERK signaling in GABA release, long-term potentiation (LTP) and learning, and show that disruption of this mechanism accounts for the learning deficits in a mouse model for Neurofibromatosis type I (NF1), a common genetic cause for learning disabilities. Genetic, pharmacological, electrophysiological and behavioral data demonstrate that neurofibromin modulates ERK/synapsin I dependent GABA release, which in turn modulate hippocampal LTP and learning. An Nf1 heterozygous null… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

40
423
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 397 publications
(468 citation statements)
references
References 44 publications
40
423
2
3
Order By: Relevance
“…In line with this conclusion, learning triggers a rapid increase in inhibitory synaptogenesis and the GABA content of inhibitory synapses [20], accompanied by long-lasting enhancement of synaptic inhibition onto excitatory neurons in mice [21]. Learning also triggers a lasting increase in GABA release from hippocampal GABAergic interneurons in mice [6,22], and learning-related feed-forward inhibitory connectivity growth in the hippocampus is required for memory precision [23]. Conversely, decreasing GABA levels in the hippocampus by overexpressing GABA transport 1 (GAT1), which is responsible for GABA reuptake after its synaptic release, impairs learning and memory in mice [24].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…In line with this conclusion, learning triggers a rapid increase in inhibitory synaptogenesis and the GABA content of inhibitory synapses [20], accompanied by long-lasting enhancement of synaptic inhibition onto excitatory neurons in mice [21]. Learning also triggers a lasting increase in GABA release from hippocampal GABAergic interneurons in mice [6,22], and learning-related feed-forward inhibitory connectivity growth in the hippocampus is required for memory precision [23]. Conversely, decreasing GABA levels in the hippocampus by overexpressing GABA transport 1 (GAT1), which is responsible for GABA reuptake after its synaptic release, impairs learning and memory in mice [24].…”
Section: Discussionsupporting
confidence: 58%
“…Hilar interneurons prevent overexcitation of granule neurons and participate in the formation and regulation of brain oscillations [4,5]. The balance of excitatory and inhibitory neuronal activity in the hippocampus, including the dentate gyrus, is thought to be required for normal learning and memory [6], while an imbalance has been implicated in the pathogenesis of amnesia in Alzheimer's disease (AD) and schizophrenia [7,8,9,10]. Although extensive research has demonstrated the importance of excitatory granule neurons in learning and memory [8], the role of hilar GABAergic interneurons remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] A bimodal intellectual quotient (IQ) distribution in the total TSC population has been suggested 7 and was recently refined as being observed only in the TSC2 population. 10 TSC patients with germline TSC1 and TSC2 mutations have only one fully functional TSC2 allele in all their cells, and this condition could lead to neurocognitive dysfunction through the mechanism of haplo-insufficiency, [14][15][16] similar to Fragile-X syndrome and Neurofibromatosis type 1. [14][15][16] However, in TSC there are additional factors which may contribute to cognitive impairment, including loss of heterozygosity, which may contribute to tuber development, 17,18 and effects of early onset and refractory epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…10 TSC patients with germline TSC1 and TSC2 mutations have only one fully functional TSC2 allele in all their cells, and this condition could lead to neurocognitive dysfunction through the mechanism of haplo-insufficiency, [14][15][16] similar to Fragile-X syndrome and Neurofibromatosis type 1. [14][15][16] However, in TSC there are additional factors which may contribute to cognitive impairment, including loss of heterozygosity, which may contribute to tuber development, 17,18 and effects of early onset and refractory epilepsy. Thus far, no associations have been found between specific TSC mutation types and cognitive outcomes, 10,19 although there are reports on associations with epilepsy and psychiatric features.…”
Section: Introductionmentioning
confidence: 99%
“…Specific deficits in the domains of visuospatial and executive functions are among the most common cognitive deficits associated with this syndrome (1,4,5). Previous mechanistic studies in a mouse model of NF1 (Nf1 heterozygous null mutants or Nf1 +/− ) demonstrated that neurofibromin modulates Rasdependent GABA release in the hippocampus, which in turn modulates long-term potentiation (LTP) and hippocampaldependent learning (6,7). However, the mechanisms underlying frontal executive dysfunction in NF1, including prominent working memory deficits (5), are unknown.…”
mentioning
confidence: 99%